2013
DOI: 10.1093/brain/aws323
|View full text |Cite
|
Sign up to set email alerts
|

New insights into genotype–phenotype correlations for the doublecortin-related lissencephaly spectrum

Abstract: X-linked isolated lissencephaly sequence and subcortical band heterotopia are allelic human disorders associated with mutations of doublecortin (DCX), giving both familial and sporadic forms. DCX encodes a microtubule-associated protein involved in neuronal migration during brain development. Structural data show that mutations can fall either in surface residues, likely to impair partner interactions, or in buried residues, likely to impair protein stability. Despite the progress in understanding the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(165 citation statements)
references
References 68 publications
7
146
0
5
Order By: Relevance
“…Cortical malformations are recovered in the human populations at a surprisingly high rate and can be familial or arise spontaneously de novo (1)(2)(3)28). One manifestation of cortical malformation is subcortical band heterotopia (SBH) and lissencephaly (LIS; smooth brain).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cortical malformations are recovered in the human populations at a surprisingly high rate and can be familial or arise spontaneously de novo (1)(2)(3)28). One manifestation of cortical malformation is subcortical band heterotopia (SBH) and lissencephaly (LIS; smooth brain).…”
Section: Discussionmentioning
confidence: 99%
“…A recent extensive study on human patients with SBH found that 100% of familial SBH is caused by mutations in the X-linked gene DCX. For de novo mutations, DCX mutations account for 50 -80% of cases (28). Both DCX-linked SBH (in females) and DCX-linked LIS (in males) are likely caused by neuronal migration defects, but axon outgrowth and guidance defects have also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that patients with less that 30% mosaicism are clinically unaffected, whereas those with more than 30% of the cells with the mutated allele are symptomatic with SBH. [3] Since the pathogenic mutation has been identified in the family, prenatal testing for pregnancies at increased risk is possible.…”
Section: Introductionmentioning
confidence: 99%